Antibody-based therapeutics and therapeutic development for diabetic retinopathy: targeting VEGF, Ang/Tie, and inflammatory pathways - Zong, Yuan; Qiu, Shuang; Zhang, Huang; Wu, Jiaxin; Du, Jingheng; Kamoi, Koju; Cen, Zhimin (Frontiers in Endocrinology, 2026)
Diabetic retinopathy (DR), a leading cause of global blindness, represents a significant microvascular complication of diabetes mellitus. This comprehensive review examines the evolving landscape of monoclonal antibody (mAb) therapy in DR management. The pathogenesis of DR involves complex molecular mechanisms including VEGF overexpression, angiopoietin dysregulation, inflammatory processes, and oxidative stress. The angiopoietin–Tie (Ang/Tie) axis is a master regulator of endothelial stability; Ang-2–driven suppression of Tie2 promotes vascular leak, pericyte dropout, and leukocyte adhesion, providing a mechanistic rationale for Ang-2 inhibition and dual VEGF/Ang-2 blockade. Anti-VEGF mAbs (bevacizumab, aflibercept, ranibizumab) have revolutionized DR treatment by effectively targeting neovascularization and vascular permeability. Recent clinical innovations include ophthalmic formulations of bevacizumab, high-dose aflibercept, the ranibizumab port delivery system, and bispecific antibodies like faricimab that simultaneously target VEGF and angiopoietin-2 pathways, alongside emerging preclinical investigations into novel targets and bio-engineered delivery platforms. While anti-inflammatory mAbs targeting IL-6, IL-17A, and IL-1β show theoretical promise, clinical evidence supporting their efficacy remains limited, positioning them as agents under therapeutic development rather than established care. Despite therapeutic advances, significant challenges persist, including cost-effectiveness concerns, treatment burden, and adherence issues. This review highlights the transformative impact of mAb therapy in DR management while acknowledging the need for continued innovation to address existing limitations and optimize patient outcomes through personalized treatment approaches.